Epilobium Species: From Optimization of the Extraction Process to Evaluation of Biological Properties - Ana-Maria Vlase; Anca Toiu; Ioan Tomuță; Laurian Vlase; Dana Muntean; Tibor Casian; Ionel Fizeșan; George Cosmin Nadăș; Cristiana Ștefania Novac; Mircea Tămaș; Gianina Crișan (MDPI AG, 2022)
Epilobium species are used in Romanian folk medicine as tinctures, tea, or tablets for ameliorating the symptoms of benign prostate hyperplasia (BPH), but scientific-based evidence is scarce for this species or other endemic plants of the same genus. Therefore, the aims of this research were to evaluate the phytochemical profile of five endemic Epilobium species (E. hirsutum L., E. parviflorum Schreb., E. palustre L. E. dodonaei Vill., and E. angustifolium L.) and to assess their in vitro biological activity. For enhanced recovery of polyphenols, a D-optimal experimental plan was developed using Modde software and the optimal working conditions were ultra-turrax-assisted extraction, for 8 min, with 30% ethanol in water. The optimized extracts were obtained from various plant parts and were further characterized by LC-MS analysis, with the major compound being oenothein B. All extracts demonstrated good antioxidant activity, evaluated by DPPH and TEAC assays. The most prominent antimicrobial potency of optimized extracts was displayed against Bacillus cereus, while against Gram-(+) bacteria, a moderate efficacy was observed. Furthermore, anti-cancer, anti-inflammatory, and antioxidant potential were assessed on normal fibroblasts and prostate carcinoma cell lines. From the evaluated optimized extracts, E. angustifolium aerial parts had the highest selectivity toward killing cancerous cells, followed by E. hirsutum aerial parts extract. For the antioxidant effect, E. hirsutum leaves and E. hirstum aerial parts extracts displayed the highest potency, decreasing ROS at the level observed for the positive control. The highest anti-inflammatory potential, based on the IL-6 and IL-8 levels, was displayed by E. dodonaei aerial parts and E. angustifolium leaves extracts. In conclusion, all five endemic species of Epilobium harvested from Romanian flora possess a diverse phytochemical composition, which supports complex biological activities.